Preparation and In Vitro Analysis of Craniofacial Titanium Implants Surfaces Produced by Additive 3D Printing and Conventional Manufacturing. Issue 3 (September 2021) - Hatamleh, Muhanad M.
Study Design: Surface finish of titanium patient-specific craniofacial implants is known to affect their acceptability and durability and relevant literature still inconclusive on the best surface finishing protocol. Objectives: This study investigated surface topography of three-dimensionally (3D) printed and conventionally manufactured craniofacial titanium implants following non-contact 3D laser profile-meter analysis. Methods: Seven groups of titanium specimens (n = 10) were prepared and their surfaces were treated differently and included sole or combined treatment of mechanical polishing, gritting with 50 micron AL2 O3, cold acid treatment using nitric acid for 20 hours (70% w/w), etching using acidic solution (69% nitric and 48% hydrofluoric acids) for 10 minutes and then electro-chemically anodized in another acidic solution (85% orthophosphoric and 98%sulphuric acid). Eighth group included specimens that were 3D printed. 3D micro-roughness parameters Sa, Sp, Sv, and Sz were determined (μm) for each specimen. Data was analyzed using one way ANOVA and Dunett T3 post-hoc tests (p < 0.05). Results: There were statistically significant effects of surface finishing protocols (p < 0.05). Sa values were 2.72-13.75 and specimens which were electroplated or mechanically polished and acid treated were the smoothest (p < 0.05). Sp was in the range 9.07-43.56 as sandblasting significantly roughened surfaces (p < 0.05). The same inferior effect was evident for the Sv (p < 0.05). The Sz values were 19.46-107.05 and was the highest for sandblasted surfaces (p < 0.05) and the lowest for surfaces of electro-chemical treatment (p < 0.05). Conclusion: Titanium surfaces are affected by the finishing procedure and electro-chemical treatment or mechanical polishing combined with acid treatment produced clinically-favorable smooth surfaces.